Guardians of Patient Safety: Nurses Shaping the Future of Infection Control - Al-Meer, Jawharh Sharf; Alsiddiq, Amal Abdullah; Alzuwairi, Ali Salman; Albadrani, Hawra Mohsin; Aljamid, Zainab Matooq; Alturaik, Maryam Radi; Shareef, Eman Saad Ahmed Al; Alamoudi, Nojoud Mohammed; Alobadi, Amro Faisal Ateeq; Ali Alharbi, Mashael Mohammed; Alsulami, Mazen Saad Muslih; Alkhaleel, Ghufran Abdulljaleel; et al. (Journal of Posthumanism, 2025)
Infection control constitutes a fundamental pillar of modern healthcare, designed to prevent and manage infections that threaten patient safety and public health. It relies on evidence-based strategies to curb the spread of infectious agents within clinical environments (Lewis et al., 2022). Healthcare-associated infections (HAIs)—including surgical site infections, pneumonia, and bloodstream infections—pose persistent challenges, increasing morbidity, mortality, and healthcare costs. Effective infection control requires rigorous implementation of practices such as hand hygiene, appropriate use of personal protective equipment (PPE), sterilization of medical instruments, and adherence to isolation protocols (Limones et al., 2020).